Literature Review: Analysis of Chatbot Trends in Government Administration - Zerlina Anggun Candrawati; Axel Arwanov Firdaus Mahaputra; Sarah Amelia Rachma (LPPM Universitas Sains dan Teknologi Komputer, 2026)
In this modern era, governments are required to provided faster, more efficient services that can be accessed anytime and anywhere. Digital transformation encourages governments to introduce service innovations, one of which is through the use of chatbots. Therefore, this study uses a Grounded Theory-based Systematic Literature Review (SLR) approach to map and analyze 100 research related to use of chatbots in the context of government administration, considering the year of publication, type of publication, sector domain, purpose of chatbot implementation, and user satisfaction level. The assessment results show that research related tor chatbots has increased sharply since 2020, with the greatest focus on the administration sector, e-government, and policies or regulations that emphasize the advantages of chatbots in providing fast, responsive, and efficient services. There are few researches that examine in depth other aspects such as the quality and accuracy of information, data security, and the level os user trust. Accordingly, subsequent researchers should focus on strengthening the quality of information, improving security and data protection, and expanding studies in sectors that have been under-researched so that the use of chatbots in government administration can develop more evenly, effectively, and sustainably.